EFEKTIVITAS BADAN KEHORMATAN DEWAN DALAM PENEGAKAN KODE ETIK INTERNAL MAUPUN EKSTERNAL DALAM MENJAGA CITRA LEMBAGA LEGISLATIF (STUDI KASUS BADAN KEHORMATAN DPRD PROVINSI JAWA TENGAH) - Wibawa, Aditya Dwi Prasetya; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2018)
The Honorary Board (BK) appears on the reformation era, the Honorary Board is a permanent equipment that is tasked with upholding the code of ethics for the members of the board. BK is one of the manifestations of the moral responsibility of council members towards the people. The formation of BK is a public spotlight on the poor performance of some members of the Board. Several cases were highlighted, such as the case of gun attacks, domestic violence and other cases. The need for integrity of the honorary body itself is very important to pay attention to.The method used in this research is qualitative descriptive. This research was conducted at the Central Java Provincial DPRD, the Honorary Board of the Central Java Provincial DPRD, the Central Java Provincial DPRD Secretariat and the Central Java Representative of the GNPK RI. Data collection techniques are carried out with interviews, documentation and literature studies.Based on the results of the study, the Effectiveness of the Board of Honor Board in Enforcing the Internal and External Code of Ethics in maintaining the image of the Legislative Institution (Case Study of the Central Java Province DPRD Honorary Agency) with the Institutional Effectiveness theory according to Martani and Lubis of the three approaches resulted in deficiencies in the three approaches because the initial approach was still less than perfect and BK has not been able to enforce a code of ethics for Board Members due to several factors.The results of this study are expected to provide good benefits for the parties involved. Based on the results of this study, the authors propose a recommendation that the requirements to become a member of the BK must be strengthened or seek figures who have good ethics and high discipline, make improvements to the rules of the Code of Ethics and Code of Conduct and increase the role of the community by providing guidance and counseling towards the community about the DPRD and the provision of guarantees of protection for people who want to complain / report violations of the Code of Ethics.Keywords: Effectiveness, Honorary Agency, Code of Ethics